THE SCIENTIFIC LINGUISTIC PICTURE OF THE WORLD IN PHILOSOPHICAL-EDUCATIONAL ASPECT - Ашиток, Н. І. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
In the article the specifics of forming of scientific linguistic picture of the world in consciousness of young people in philosophical and educational aspectsare examined, problems which arise up during this process are probed.